RESPONSE TO THE USE OF STORYTELLING IN THAI MUSEUMS: THE CREATION OF ‘SACRED SPACE’ IN ARCHITECTURE RELATES TO THE IMAGE OF THE BUDDHA IN THAILAND COULD BE POLITICAL - Deesawadi, Nalinnath (PEOPLE: International Journal of Social Sciences, 2017)
If ‘sacred symbol' causes the image of the Buddha to be ‘sacred,' what does this occurrence effect space surrounding them? In Thailand, the creation of the image of the Buddha is an extraordinary achievement both visually and in its motive. The image of the Buddha is also believed to be a ‘sacred symbol’ with a ‘sacred space’; but how does this belief affect us as spectators. How can we understand a proper meaning of the image of the Buddha when we are at the museum not at the site? In this article, I have questioned and discussed that the storytelling of the image of the Buddha in a museum should be shown significantly because of the ordinary existence of its ‘sacred space. Whether ‘sacred space' was political and still exists or no longer exists, it is, nevertheless, a representation of past human belief. It is also essential to convey storytelling accurately and that designing area in the museum will largely affect the audience. In this writing, I focus on the use of storytelling in Thai museums; case study why the creation of ‘Sacred space’ in architecture relates to the image of the Buddha in Thailand cloud be political. The article aims to respond to development plans of museums in Thailand. As a result, the interpretation of ‘Sacred space' in architecture relates to the image of the Buddha can apply to installation and space design in the museums. With a proper storytelling of the image of the Buddha, this can help spectators to understand better in Thai histories, political influences on arts and will lead Thai people to feel to preserve their art properties.